The Effect of Acupressur Therapy on Hyperemesis Gravidarum in Trimester I Pregnant Woman Aceh 2022 - Nur Azizah; Rusmei Yanti Gultom (Institute of Computer Science (IOCS), 2022)
Emesis gravidarum is a common complaint that occurs in early pregnancy. Most nausea and vomiting during pregnancy can be treated with oral medications, as well as sedatives and anti-emetics. However, a small proportion of pregnant women cannot cope with ongoing nausea and vomiting, which interferes with activities and causes electrolyte imbalance due to lack of fluids. (Manuaba et al., 2015).The purpose of this study was to analyze the effect of giving Ambon bananas to increase hemoglobin levels in adolescents at Central Aceh STAR Health Center in 2022. Types of research used in this research is quantitative research with Quasy Experiment research design with Two Group with pre test post test design which consists of 2 groups, control group and experimental group. This research was conducted at Central Aceh STAR Health Center A total of 65 people with a total sample of 28 people who have anemia. The sampling technique used is purposive sampling. Bivariate analysis using Mann Whitney statistical test. This study obtained the results of P-Value 0.035 (P <0.05) it was stated that there was an effect between acupressure on reducing nausea and vomiting in pregnant women after acupressure therapy was carried out.